2005
DOI: 10.1254/jphs.fp0050564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anti-Nerve Growth Factor Antibody on Symptoms in the NC/Nga Mouse, an Atopic Dermatitis Model

Abstract: Abstract. Nerve growth factor (NGF) is an important substance in the skin, where it can modulate nerve maintenance and repair. However, the direct link between NGF and pruritic disease such as atopic dermatitis is not yet fully understood. To determine whether NGF plays a major role in atopic dermatitis and in the development or maintenance of skin lesions, we performed a study using NC / Nga mice and compared mice with and without skin lesions. Our examinations of the NC / Nga mice sought to detect nerve fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 65 publications
2
64
1
2
Order By: Relevance
“…Intraperitoneal administration of anti-nGf neutralizing antibody to atopic nc/nga mice significantly attenuated both the increased number of nerve fibers in the epidermis and scratching behavior, but did not ameliorate scratching that had already developed. 52) Similarly, application of the TrkA antagonists AG879 and K252a to the nape of atopic nc/nga mice significantly improved established dermatitis and scratching behavior and reduced the numbers of nerve fibers in the epidermis, suggesting the importance of nGf in the pathogenesis of atopic dermatitis-like skin lesions. 53) thus, nGf and its receptors may be among the antipruritic targets in pruritic skin diseases such as atopic dermatitis.…”
Section: Anti-ngf Antibody and Ngf Receptor Antagonistsmentioning
confidence: 93%
“…Intraperitoneal administration of anti-nGf neutralizing antibody to atopic nc/nga mice significantly attenuated both the increased number of nerve fibers in the epidermis and scratching behavior, but did not ameliorate scratching that had already developed. 52) Similarly, application of the TrkA antagonists AG879 and K252a to the nape of atopic nc/nga mice significantly improved established dermatitis and scratching behavior and reduced the numbers of nerve fibers in the epidermis, suggesting the importance of nGf in the pathogenesis of atopic dermatitis-like skin lesions. 53) thus, nGf and its receptors may be among the antipruritic targets in pruritic skin diseases such as atopic dermatitis.…”
Section: Anti-ngf Antibody and Ngf Receptor Antagonistsmentioning
confidence: 93%
“…In this study, tacrolimus and RG (1%) inhibited DNFB-induced NGF mRNA expression. In consideration of the previous report (35), NGF seems to be an important regulator of nerve fiber extension.…”
Section: Discussionmentioning
confidence: 71%
“…It has also been reported that NGF is abundantly released from human keratinocytes in vitro (34) and highly expressed in the epidermis of NC/Nga mice (35,36). Furthermore, in NC/Nga mice, treatment with an anti-NGF antibody abolished nerve fiber extension as well as skin lesions (35).…”
Section: Discussionmentioning
confidence: 94%
“…In fact, high-affinity NGF-receptor inhibitors, AG879 and K252a, are effective in improving the established dermatitis (50) and scratching behavior in the NC/Nga atopic dermatitis model mouse (51), and anti-NGF antibody is also effective in inhibiting epidermal innervation and scratching in NC/Nga mouse (52). However, complete interception of NGF signaling may cause some side effects because autocrined NGF is thought to be involved in keratinocyte proliferation and important for normal elongation of neuronal fibers.…”
Section: Discussionmentioning
confidence: 99%